2013
DOI: 10.1016/j.ultsonch.2012.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Compare study CaCO3 crystals on the cellulose substrate by microwave-assisted method and ultrasound agitation method

Abstract: The purposes of this article were to investigate the influences of synthesis strategy on the CaCO(3) crystals on the cellulose substrate. In this study, CaCO(3) crystals were synthesized using cellulose as matrix by the microwave-assisted method and ultrasound agitation method, respectively. The CaCO(3) crystals on the cellulose substrate were characterized by means of X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). Experimental results demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…High efficiency for CR removal using calcium-rich fly ash (Acemioglu 2004) and Cabentonite (Lian et al 2009) has also been reported previously. CaCO 3 -loaded cellulose composites have been produced using microwave- (Stoica-Guzun et al 2013) and ultrasound-assisted methods (Fu et al 2013), in which the composite samples were characterized in terms of cytotoxicity and mechanical properties, respectively. In this study, we produced CaCO 3 -cellulose aerogel by in situ synthesis of CaCO 3 in as-produced cellulose aerogel.…”
Section: Introductionmentioning
confidence: 99%
“…High efficiency for CR removal using calcium-rich fly ash (Acemioglu 2004) and Cabentonite (Lian et al 2009) has also been reported previously. CaCO 3 -loaded cellulose composites have been produced using microwave- (Stoica-Guzun et al 2013) and ultrasound-assisted methods (Fu et al 2013), in which the composite samples were characterized in terms of cytotoxicity and mechanical properties, respectively. In this study, we produced CaCO 3 -cellulose aerogel by in situ synthesis of CaCO 3 in as-produced cellulose aerogel.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose/AgCl hybrids with excellent antimicrobial activity were synthesized using cellulose solution and AgNO 3 in N,N-dimethylacetamide solvent (Li et al, 2012). Cellulose/CaCO 3 hybrids with good biocompatibility were synthesized using cellulose, CaCl 2 , and Na 2 CO 3 in ethylene glycol (Fu, Dong, Ma, Li, & Sun, 2013). Bacterial cellulose/hydroxyapatite hybrids with a 3-dimensional network were fabricated by a biomimetic process (Wan et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of these processes, which occurred during the nanocellulose preparation, the obtained non-sonicated sample was highly flocculated. The ultrasounds, besides of nanocellulose particles fragmentation favor the CaCO 3 crystals synthesis what could increase homogeneity of nanocellulose/PCC systems in respect to the particles size (Fu et al 2013).…”
Section: Mechanical Properties Of Nanopapersmentioning
confidence: 99%